Application of the MOORA method for the management of the workload in the care of patients with COVID-19 - López Castañeda, Jesús Raymundo; Pérez-Domínguez, Luis Asunción; García Alcaraz, Jorge Luis (Unidad Editorial UPTC, 2021)
Abstract The COVID-19 pandemic was difficult for everyone and even more so for hospitals and medical personnel. The infections caused by this disease were many in a very short time, due to this, hospitals resorted to using engineering tools for effective and efficient management of patients with severe symptoms of COVID-19. Considering the above, it is possible to apply a multi-criteria decision method to prioritize the objectives that must be met to achieve the best medical care for patients with severe symptoms. The results obtained is that the criterion that should be approached first is the use of digital communication platforms such as WeChat, Whatsapp, Telegram, because these platforms offer instant communication through text, images, documents, videos or audios and which does not require physical presence between the isolation room and the outside, compared to those obtained at Huazhong University, this method would define the order of priority in which these objectives should be achieved. Finally, the results obtained depict that it is possible to prioritize the management of workloads in the care of patients with COVID disease. Keywords MOORA, Likert scale, PDCA, COVID-19. JEL codes: D14, D61, I31, O33, 035, P18. Received: 04/04/2021. Accepted: 26/07/2021. Published: 18/12/2021.